Analysis of Listening Material in Senior High School Students’ Textbook - Darman Pangaribuan; Stefani Agustina Silalahi; Anggie Pratiwi; Elfian Manalu; Erikson Saragih (EDUCARE, 2019)
Listening is one of the basic skill in language. The process of listening is to notice, identify and understand what others are saying. Pathway to English is Students’ Textbook used for Senior High School Grade eleven. This textbook includes listening material. Therefore, the researchers are interested in conducting a research related to the strengths and weaknesses of the Textbook. This research used qualitative method. The instruments of the research is observation. The result of the study shows that there are some strengths and weaknesses of the listening material in this textbook. These weaknesses may affect to the output of language learning and cannot develop students’ skill. Therefore it is hoped that the teacher should pay more attention on the listening material in order to help students gain the skill.